The Role of Government’s Social Media to Enhance Environmental Awareness - Syofriyeni, Nini; Kartika, Rayna (Universitas Negeri Semarang, 2023)
Environmental awareness is an important aspect to create a clean environment. One of the best alternatives to encourage society to have environmental awareness is by promoting and introducing the importance of carbon mitigation and energy saving through campaigns on the government’s social media. This paper aims to test empirically to what extent the determinant of information in government campaigns on so cial media affects the quality of information on the government’s social media. The determinants of information used in this paper are relevant, reliable, timely, and complete. This research is a quantitative descriptive approach where the data is obtained through questionnaire distribution to Facebook, Twitter, and Instagram users from July to December 2022. The data is analyzed by multiple regression model using SPSS. To address this, there are 205 questionnaires collected in this research. The findings show that relevant and complete have effects on the quality of information while reliable and timely do not have effects on the information quality. In addition, the practical implication of the research is also discussed in this paper.